Phenolics from Abies cephanolica and Abies borisii-regis - Couladis, Maria; Mabry, Tom; Verykokidou, Evmorfia (Asian Journal of Chemistry, 2010)
In the present notes, the authors describe the extraction and characteristics of phenolics from Abies cephanolica and Abies borisii-regis.